1964
DOI: 10.1121/1.1919255
|View full text |Cite
|
Sign up to set email alerts
|

Loudness Function of a 1000-cps Tone in the Presence of a Masking Noise

Abstract: Loudness levels of a partially masked 1060-cps tone are determined by loudness-balance procedures and, indirectly, by the methods of magnitude estimation and production. It is shown that loudness balances obtained by the method of adjustment are consistent with the loudness judgments obtained by the combined method of magnitude estimation and production, called method of numerical magnitude balance. The final results are in good agreement with those of other investigations in which balanced procedures were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
2

Year Published

1972
1972
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(61 citation statements)
references
References 0 publications
9
50
2
Order By: Relevance
“…By this token, I would expect greater bias when the stimuli being compared differ in quality than when they differ in some other way, even if the differences in dissimilarity are equal. Therefore, the present results are consistent with the contention that the data obtained from scaling experiments such as those of Hellman and Zwislocki (1964), Raab (1962), J. C. Stevens and Hall (1966), and J. C. Stevens and S. S. Stevens (1963), which required subjects to judge stimuli that varied on nonqualitative dimensions, yielded "good" matches, in that the matching stimulus values are not highly susceptible to "contextual bias. "…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…By this token, I would expect greater bias when the stimuli being compared differ in quality than when they differ in some other way, even if the differences in dissimilarity are equal. Therefore, the present results are consistent with the contention that the data obtained from scaling experiments such as those of Hellman and Zwislocki (1964), Raab (1962), J. C. Stevens and Hall (1966), and J. C. Stevens and S. S. Stevens (1963), which required subjects to judge stimuli that varied on nonqualitative dimensions, yielded "good" matches, in that the matching stimulus values are not highly susceptible to "contextual bias. "…”
Section: Resultssupporting
confidence: 80%
“…The success reported by J. C. Stevensand S. S. Stevens (1963), by Hellman and Zwislocki (1964), and by others lends support to the contention that magnitude estimates do provide accurate sensory matches when stimuli differ along dimensions other than quality. Stevens and Stevens compared the brightness aroused by white-light stimulation of a dark-adapted eye and of a white light-adapted eye; presumably, the various test stimuli varied greatly in brightness but only slightly in color.…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…1 and 2, for they provide a more complete picture of the extent of the asymmetry. The intersection of the loudness-matching functions with the eq ual SPL line is clearer than when noise is the masker (Hellman & Zwislocki, 1964;Hellman, 1970). The difference is probably due to the strong dominance of noise as a masker.…”
Section: Resultsmentioning
confidence: 86%
“…The rate of loudness growth in the impaired ear is often so steep that, at high intensities (60-100 dB SPL, e.g., Stillman et al 1993), the loudness in the impaired ear matches that in the normal one. Loudness recruitment has been primarily studied in humans (e.g., Miskolczy-Fodor 1960;Hellman and Zwislocki 1981;Moore et al 1985;Zeng and Turner 1991) and has also been demonstrated in behavioral animals with SNHL (Pugh et al 1979). …”
Section: Introductionmentioning
confidence: 99%